THE EFFECT OF LIQUIDITY (LOAN TO DEPOSIT RATIO) AND PROFITABILITY (RETURN ON ASSETS) ON COMPANY VALUE (PRICE TO BOOK VALUE): A STUDY OF BANK KBMI IV, LISTED ON THE INDONESIA STOCK EXCHANGE (IDX), 2020–2025 - Dhita Febriyanti; Ari Bramasto; Taufik Sadikin (International Journal Management and Economic, 2026)
This study aims to determine the effect of Liquidity (Loan to Deposit Ratio) and Profitability (Return on Assets) on Company Value (Price to Book Value) at Bank KBMI IV listed on the Indonesia Stock Exchange for the period 2020-2025. This study uses secondary data in the form of quarterly financial reports. The method used is the Quantitative method with census techniques. The data analysis techniques used are Descriptive and Verification analysis using Panel Data Regression, Classical Assumption Test, Determination Coefficient Analysis, and Hypothesis Testing. In analyzing the data, this study used Eviews 14 software. The results of this study indicate that the Loan to Deposit Ratio has a negative and significant effect on Price to Book Value. Meanwhile, Return on Assets has a positive and significant effect on Price to Book Value. Simultaneously, the Loan to Deposit Ratio and Return on Assets have a significant effect on Price to Book Value. This finding implies that a company's ability to manage liquidity and generate profits is an important factor that influences company value in the eyes of investors.